Multi-omic identification of perineurial hyperplasia and lipid-associated nerve macrophages in human polyneuropathies - Michael Heming; Anna-Lena Börsch; Jolien Wolbert; Christian Thomas; Anne K. Mausberg; Fabian Szepanowski; Bianca Eggert; I-Na Lu; Julia Tietz; Finja Dienhart; Maja Meschnark; Jan-Kolja Strecker; et al. (Nature Communications)
Abstract Diseases affecting multiple peripheral nerves, termed polyneuropathies (PNPs), are common, mechanistically heterogeneous, and their causes are challenging to identify. Here, we integrated single-nucleus transcriptomics of peripheral nerves from 33 human PNP patients and four controls (365,708 nuclei) with subcellular spatial transcriptomics. We identified nerve cell type markers and uncovered unexpected heterogeneity of perineurial cells. PNPs shared a loss of myelinating and an increase in repair Schwann cells and endoneurial lipid-phagocytizing macrophages. Transcriptional changes affected multiple cells outside of the endoneurium across PNPs, suggesting PNPs as ‘pan-nerve diseases’. Spatially, PNPs—particularly those mediated by autoimmunity—exhibited focal perineurial hyperplasia and increased expression of CXCL14, identified as perineurial cell marker. Multi-omic characterization of human nerve biopsies thus identified novel mechanisms in PNPs with diagnostic potential.